Pengembangan Sistem Kelistrikan Tanah Merah Mempertimbangkan Energi Baru Terbarukan dan Emisi CO2 - Amrisal Kamal Fajri; Sarjiya; Lesnanto Multa Putranto; Adlan Bagus Pradana; Fransisco Danang Wijaya (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
The condition of the electricity system in the Papua region still has an electrification ratio of 94% with a high electricity generation cost of IDR3,041/kWh. In addition, the existing electricity system still consists of over 100 small systems, the majority of which are diesel power plants. One of the systems is the Tanah Merah area, with a population of 19,136 people and an energy demand of 6.89 GWh. The region is projected to experience expansion and population growth, resulting in a corresponding rise in the demand for electrical energy. Therefore, planning for the development of power plant systems needs to be done to meet the growing demand for electrical energy. Planning in remote areas is typically done for a short-term timeframe spanning from 2025 to 2030, involving the optimization process of several proposed power plant candidates. The proposed candidate power plants consider gas and fuel supply, as well as the availability of local primary energy and technology. Optimization will minimize the total cost of the to-be-selected power plant, which has features including initial investment costs, ongoing operation and maintenance costs, fuel expenses, and the residual value of the assets throughout the planned duration. In planning, a greenhouse gas emission reduction of 29% and an energy mix proportion of 23% need to be considered in accordance with government policy. Therefore, two scenarios covering both economic and environmental aspects were considered in the simulation process, namely the business as usual (BaU) scenario and the nationally determined contributions (NDC) scenario for emission limitation. Optimization was developed based on mixed-integer linear programming (MILP) performed in HOMER software. The simulation results indicate that the electricity generation cost for the BaU scenario is more economical compared to the NDC scenario at IDR2,559.8/kWh versus IDR3,104.64/kWh.